A framework for consistences in association relations between classes in uml (2014)
The following article shows the process of building and validating a framework for the management of consistencies in class diagrams in UML, operating specifically on class diagrams, through the application of transformation rules, using both graph grammar and OCL (Object Constraint Language). The proposed framework, after examining the techniques of consistency management, operates on a class diagram, since this constitutes a structural diagram. This is even more important when modeling, and it facilitates the application of rules based on the treated techniques, thus contributing to provide the community of analysts and modelers with a support tool for the refinement and quality improvement of the diagrams. It also operates on a typical case of application to show the tool’s advantages, thus making it easier to comprehend and understand.